The effect of body mass index on high versus low administered activity protocol myocardial perfusion imaging scan time and effective dose using a cadmium zinc telluride camera in clinical practice - Prasad, Kalpna; Adams, Chad C.; Quang, Eiping; Taylor, Justin; Stocker, Derek J. (World Journal of Nuclear Medicine, 2021)
Cadmium Zinc Telluride (CZT) crystal-based myocardial perfusion imaging (MPI) cameras have increased count sensitivity compared to Anger cameras and can be used to lower either the injected activity or the image acquisition time. Institutions adopting CZT cameras need to decide whether to lower the injected activity or imaging time or attempt to lower both with a compromise. The aim of our study was to compare the scan time required to obtain similar count images using high activity protocol (HAP) versus low activity protocol (LAP) stratified by body mass index (BMI) and assess the impact on effective dose and our clinic workflow. Using a CZT camera, a cohort of 100 consecutive clinical patients imaged with LAP rest-stress MPI with approximately 185 MBq and 555 MBq activity was retrospectively compared to a similar cohort of 100 consecutive clinical patients imaged with HAP rest-stress MPI using approximately 370 MBq and 1110 MBq. Administered activity and BMI both had a statistically significant effect on scan time and radiation effective dose. LAP scans took an average of 9 min longer than HAP scans overall, P < 0.0001 and larger BMIs took longer than smaller BMIs, P < 0.0001. In addition, scan times were longer in men than women, P = 0.007. Effective dose was inversely proportional to BMI with an overall decrease of approximately 50% comparing LAP to HAP. For the same CZT camera, the LAP increased scan time while lowering the radiation effective dose when compared to HAP. The increase in scan time increased proportionally to BMI. The effective dose was inversely proportional to BMI. This increase in time did not have a significant impact on our local workflow, but its implications should be considered in the setting of LAP implementation, especially in obese or high patient volume practices.
Keywords: Body mass index; cadmium zinc telluride camera; low dose; myocardial perfusion imaging; radiation exposure; scan time